2016
DOI: 10.4314/ujas.v16i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common gastro-intestinal nematode infections in commercial goat farms in Central Uganda

Abstract: Gastro-intestinal nematode (GIN) infections are the leading cause of production losses in commercial goat farms worldwide. This study determined the level of gastro-intestinal nematodes (GIN) infection and identified the common GIN parasites in commercial goat production in Central Uganda. Faecal egg counts and morphological larval identification in coprocultures were used to estimate the burden of common GIN of goats in Central Uganda. Egg shedding was detected in 43% of the goats. Worm burdens were highest (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
6
10
1
1
Order By: Relevance
“…infection in goats (71.3%) than sheep (67.57%) was reported [ 29 ]. Studies in neighbouring Uganda have reported the prevalence of goats shedding nematode eggs at 53.7% [ 10 ] which is lower than that reported in this study. This may be explained by the differences in management practices such as stocking density and ecoclimatic factors.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…infection in goats (71.3%) than sheep (67.57%) was reported [ 29 ]. Studies in neighbouring Uganda have reported the prevalence of goats shedding nematode eggs at 53.7% [ 10 ] which is lower than that reported in this study. This may be explained by the differences in management practices such as stocking density and ecoclimatic factors.…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, they lead to forced culling, carcass, and organ condemnations [ 9 ], increased cost of veterinary treatments, decreased weight gain, reduced milk production and reproductive capacity, decreased work capacity, diminished food intake, reduced animal growth rates, and lower weight gains and treatment and management costs [ 8 12 ]. Among these gastrointestinal helminths, nematodes are the leading cause of ill-health and production losses in sheep and goats worldwide [ 7 , 10 , 13 ]. It would appear that a number of reports point to Trichostrongylid nematodes, especially Haemonchus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, studies that have attempted to investigate the epidemiology of gastro intestinal parasitic infections (GIP) in small ruminants have largely concentrated on nematodes, though, grazing goat are invariably infected with several of gastrointestinal parasites. For instance, Nsereko et al (2015) researched about nematodes and reported prevalence of 43% in goats while Magona and Musisi (2002) focused on strongyloidosis and revealed a significantly high prevalence of 73.3%. These findings have not been explicit and provide limited information on the situation of gastrointestinal parasites infections in small ruminants, particularly the magnitude and extent of infection rate.…”
Section: Introductionmentioning
confidence: 99%
“…Helminthosis (diseases including those caused by nematode parasites) is the most important livestock disease in most tropical countries (Khan et al 2010 ; Lapenga et al 2009 ; Perry et al 2002 ; Vatta and Lindberg 2006 ). The most prevalent of GINs in Uganda is H. contortus (Nsereko et al 2015 ). GIN particularly H. contortus has a high fecundity and is a debilitating blood-sucking parasite in the abomasum causing significant production losses through severe chronic anemia, anorexia, loss of condition, and eventual death of the affected animals (Notter et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%